Comparison of Current Perception Thresholds Using PainVision and Neurometer in Patients with Oromaxillofacial Hypoesthesia: Pilot Study - Jee-Won Jang; Hye-Mi Jeon; Kyung-Hee Kim; Hye-Min Ju; Soo-Min Ok; Sung-Hee Jeong; Yong-Woo Ahn (Korean Journal of Legal Medicine, 2026)
Iatrogenic injuries to the inferior alveolar and lingual nerves during dental procedures require objective sensory evaluation. While the Neurometer is established for oromaxillofacial physical evaluation, PainVision is a novel device that measures pain equivalent current. However, its reference values are limited to extremities, with none established for the oromaxillofacial region. This retrospective pilot study evaluated the practical utility of PainVision by comparing its current perception threshold (CPT) with the Neurometer, aiming to determine preliminary cut-off values for diagnosing hypoesthesia. We measured and compared CPTs between affected and contralateral normal sites in 32 patients with unilateral sensory alterations using both devices. CPT values at the affected site were significantly higher across all measurements (P